Pruritus and Cutaneous Lesions: Granuloma Annulare vs. Mycosis Fungoides in a Patient with Comorbidities. A Case Report - Flores-Sáenz, Manuel (2024)
Introduction: Pruritus is a common symptom in dermatological practice. Affecting patients with a wide range of cutaneous and systemic diseases. It can be caused by cutaneous disorders, systemic diseases, neurological disorders, psychological disorders, medications, among others. When assessing individuals with pruritus and cutaneous lesions, it is essential to consider mycosis fungoides and granuloma annulare as noteworthy differential diagnoses. Case presentation: A 51-year-old female patient exhibited symptoms of pruritus and two occurrences of pruritic skin lesions. Accompanied by a low-grade fever measuring 37.7 ºC, as well as asthenia and myalgia. Physical examination revealed two rounded plaques with erythematous borders and multiple non-confluent papular lesions. Discussion: Differentiating between mycosis fungoides and granuloma annulare can be challenging due to the similarities in their clinical presentations. However, performing a biopsy is essential to reach a definitive diagnosis. Conclusions: A biopsy is being suggested for the front part of the left lower limb. The application of mometasone furoate twice a day for two weeks was prescribed. Subsequently, a meeting has been arranged to conduct a review and to carefully analyze the biopsy findings within thirty days.